2016
DOI: 10.1155/2016/9309534
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Perspectives of Complementary and Alternative Medicine among University Students in Atlanta, Newcastle upon Tyne, and New Delhi

Abstract: Objective. A cross-cultural comparative study was developed that surveyed university students in Atlanta (United States), New Delhi (India), and Newcastle upon Tyne (United Kingdom) to understand the prevalence and perspectives of CAM in three urban societies with different healthcare systems. Design. Surveys were sent to students in the three aforementioned cities. Survey distribution occurred over 6 months from May to November 2015. A total of 314 surveys were received. Results. Dietary and vitamin supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Previous studies about CAM use in university students in the US, India, and the UK reported the similar results that reasons for CAM use were maintenance of physical and mental fitness [7], stress, maintenance of health, and nutrition [6]. Our results also indicate that compared to Korean older adults, Korean young adults presumably have different reasons for CAM use: A previous study reported that the most common reason for CAM use was “lack of energy” followed by “disease prevention” in Korean older adults (30-69 years) [18].…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies about CAM use in university students in the US, India, and the UK reported the similar results that reasons for CAM use were maintenance of physical and mental fitness [7], stress, maintenance of health, and nutrition [6]. Our results also indicate that compared to Korean older adults, Korean young adults presumably have different reasons for CAM use: A previous study reported that the most common reason for CAM use was “lack of energy” followed by “disease prevention” in Korean older adults (30-69 years) [18].…”
Section: Discussionmentioning
confidence: 63%
“…were found to be most prevalent among the students. Considering the unique health care systems of the three countries, it was concluded that 55% of Indian students considered CAM as a more affordable approach than routine healthcare practices [32].…”
Section: Yoga As Cammentioning
confidence: 99%
“…Therefore, the term Complementary and Alternative Medicine (CAM) encompasses a wide variety of therapies and systems. The popularity of certain CAM therapies in certain countries or ethnic populations can be attributed to cultural factors such as religion [3]. Some CAM practices, such as meditation and yoga, are popular due to the fact that there are no negative side effects [4].…”
Section: Introductionmentioning
confidence: 99%
“…They all reported that most students had positive attitudes towards CAM, were interested in training in CAM practices, and were open to using or recommending CAM methods to their patients in their future professional lives. Studies on the use of, attitude toward, and knowledge of CAM in general student populations or health professional students from around the world paint a picture of great diversity shaped by cultural and societal factors [3,[15][16][17]. For example, a study surveying university students in Atlanta (USA), New Delhi (India), and Newcastle upon Tyne (UK) found that the use of whole medical systems, such as ayurveda and homeopathy, was more prevalent among the students in New Dehli [3].…”
Section: Introductionmentioning
confidence: 99%